Reading drills Jamestown's reading improvement - Fry, Edward B. (Jamestown Pub., 2000)
"Reading Drills" is for students who want to read faster and with greater understanding. By completing the 30 lessons -- reading the selections and doing the exercises -- you will certainly increase your reading speed, improve your reading comprehension, and sharpen your critical-thinking skills.